Study of anticholinesterase properties of loratadine and desloratadine - Smishko, Roman; Lyzhniuk , Viktoriia; Lisovyi , Vadym; Kharytonenko , Hanna; Bessarabov, Volodymyr (Annals of Mechnikov’s Institute, 2025)
Given that antihistamines are among the most commonly used drugs among different age groups, availability and low cost of drugs, it is important to have complete information about their pharmacological profile and pleiotropic effects. The identification of new pharmacological properties of antihistamine active pharmaceutical ingredients (APIs) may help to expand the indications for their use, improve treatment efficacy and reduce the risk of adverse reactions associated with polypharmacy. The aim of the work is to investigate and compare the effect of the antihistamine active pharmaceutical ingredients loratadine and desloratadine on the activity of the enzyme butyrylcholinesterase (BChE) in human serum. Materials and methods. The activity of butyrylcholinesterase and the effect of the antihistamine active pharmaceutical ingredients loratadine and desloratadine on this enzyme were determined ex vivo spectrophotometrically at a wavelength of 405 nm using the modified Ellman method. Experimental data processing included the calculation of steady-state velocities and kinetic parameters of inhibition and was performed according to standard methods. The kinetic characteristics of the studied process were analyzed and visualized in the SigmaPlot 14.0 software package. Results. It was found that both loratadine and desloratadine are dose-dependent inhibitors of butyrylcholinesterase. Both antihistamines reduce the maximum rate of the enzymatic reaction and increase the Michaelis constant, which fully corresponds to the effect of mixed (partial) inhibition. It was established that for loratadine the concentration required to achieve 50% inhibition of butyrylcholinesterase is IC50 = 117.782 ± 10.013 μM, and for desloratadine – 131.403 ± 13.025 μM. Conclusions. Given that human serum butyrylcholinesterase is involved in the metabolism of a number of APIs, including muscle relaxants and local anesthetics of the ether type, which causes their rapid inactivation and short-term effect, the inhibitory activity of loratadine and desloratadine against this enzyme is important for modifying the pharmacokinetic parameters of these compounds. The data obtained can serve as a basis for further studies aimed at studying the rate of decomposition of muscle relaxants and local anesthetic compounds by butyrylcholinesterase when used in combination with antihistamines.